Scanning Technologies Adoption for Transtibial Residual Limb Shape Characterization - Sarah Duraid AlQaissi; Ahmed A.A. AlDuroobi; Abdulkader Ali. A. Kadaw (Journal of Engineering and Sustainable Development)
In prosthetics, 3D scanning technology plays a crucial role in gathering data for designing prosthetic devices. New tools for capturing the external shape of human body parts are rapidly emerging. This study conducted a comparative analysis to assess the accuracy and precision of two handheld 3D scanners, including the Peel 3 3D scanner and a smartphone application, in scanning the residual limb of a transtibial participant. The residual limb was manually measured, and six scans were taken with each scanning system, compared to the reference computed tomography (CT) model. A repetition test was performed to determine the mean value and standard deviation of the scanned models in VXelements software for comparison purposes. The results showed a standard deviation difference between the Peel 3 and CT scans ranging from ± 0.828 to 0.907mm, and from ± 0.823 to ± 0.877mm for the smartphone scans. The repetition test indicated standard deviations ranging from ± 0.531 to 0.599 mm for the Peel 3 and ± 0.458 to 0.690 mm for the smartphone. This analysis evaluated the accuracy of the 3D scanners and identified the essential specifications for their effective use in prosthetics.